A revision of genus Vatica L. (Dipterocarpaceae) in Borneo I:Taxa in Sabah and Sarawak - Meekiong, K.; Latiff, A (Malayan Nature Society, 2021)
A taxonomic revision of the genus Vatica L. (Dipterocarpaceae) in Borneo focusing on taxa Sabah and Sarawak is presented herein. A total of 46 taxa from 40 species is recognised and grouped into three sections. The sections are sect. Vatica 17 taxa (12 species), sect. Sunaptea 22 taxa (21 species), sect. Pachynocarpa with four species, and Vatica pentandra which has five stamens is not placed in any section due to lack of information of the fruit calyx characteristics. Full descriptions of species are excluded as they are presented elsewhere.